(untitled) (International Journal of Environmental Sciences, 2025)
Women with disabilities face compounded challenges in employability due to the intersection of gender and disability-related discrimination. This study investigates whether differently abled women experience greater employment disadvantages compared to their male counterparts and other marginalized groups. Drawing from psychological theories such as Stigma Theory, Social Identity Theory, Self-Efficacy Theory, and Stereotype Threat Theory, the study explores how societal biases, workplace exclusion, and internalized perceptions of capability impact their employability. The research employs a mixed-methods approach. A sample of 262 respondents was analyzed using ANOVA to determine gender-based disparities in employment-related challenges. While findings indicate no significant gender difference in overall employability challenges, financial constraints, hiring issues, or workplace biases, significant disparities exist in employment accessibility and skill development opportunities, with women facing greater barriers. These findings align with global literature on the compounded disadvantages faced by women with disabilities due to deep-rooted societal norms, limited vocational training, and lack of targeted policy interventions. The study underscores the need for inclusive employment policies that specifically address gendered barriers faced by women with disabilities. It calls for targeted interventions such as accessible skill development programs, mentorship opportunities, and employer sensitization programs to foster equitable workplace environments. By shifting focus from broad gender-neutral policies to intersectional approaches that consider both gender and disability, policymakers and organizations can better promote economic independence and workplace inclusion for differently abled women.